An Assessment Of Physicochemical Properties, Heavy Metal Enrichment And Fungal Characterization Of Refined Kerosene Impacted Soil In Anand, Gujarat, India - Khan, Shamiyan R; Kumar, JI Nirmal; Kumar, Rita N; Patel, Jignasha G (International Journal of Environment, 2013)
The present study was carried out to assess the physico-chemical properties, heavy metal enrichment and fungal isolation and characterization of the top soil samples collected in-situ from aged refined kerosene contaminated as well as uncontaminated garden soil sites in Anand, Gujarat, India. The total petroleum hydrocarbon (TPH) concentrations were 17,510 mg/kg in kerosene contaminated soil against 142.65 mg/kg for uncontaminated soils. The contamination increased the soil organic carbon, nitrogen and clay to 2.95 %, 0.612 %, 36.22 % as compared to 1.5%, 0.153%, 32.4% respectively in the uncontaminated soil. Increased concentration of heavy metals like Cobalt, Copper, Iron, Zinc and Lead against the uncontaminated soil was encountered. Ten native fungal speciesbelonging to a total of five genera include Aspergillus (A. terreus, A. versicolor, A. niger); Fusarium oxysporum; Penicilliumjanthinellum from the uncontaminated garden soil, whereas the contaminated soil included Aspergillus (A. terreus, A. versicolor , A. niger) Candida tropicalis,Cladosporiumbruhnei and Fusarium oxysporum, identified based on 18S rRNA and the nucleotide sequences were submitted to the NCBI, GenBank database. The changes created by kerosene contamination resulted in variation in individual concentrations of physicochemical properties, soil conductivity, pH and soil fertility indices probably dwindle the growth of fungal strains causing a reduction in the fungal population in the kerosene contaminated soil. International Journal of Environment, Volume-2, Issue-1, Sep-Nov 2013, Pages 164-174 DOI: http://dx.doi.org/10.3126/ije.v2i1.9219